Transformational Leadership and Development of Marketing Capabilities: Mediating Role of Market and Entrepreneurship Orientation - Mohammad Naji, Iman Hakimi, Leila Sharifipour (International Journal of Advanced Science and Technology, 2019)
Failure to adapt to the rapid and broad changes in the current business environment, can negatively impact the performance of organizations. As such, organizational capabilities and processes need to be developed, extended and/or renewed. Meanwhile, marketing capabilities play a vital role in the superior performance of organizations, and their development is significantly influenced by strategic orientations as a combination of resources, behavioral patterns and value points of a business in the market. On the other hand, the necessity of continuous organizational changes in a dynamic and changing environment today is the presence of transformational leaders. Therefore, the present study tries to examine the relationship between transformational leadership, marketing capabilities and organizational performance by mediating the strategic orientations of entrepreneurship and market orientation, from the perspective of senior executives of small & medium enterprises in the food industry of Kerman Province in the first six months of 2017. The data gathering tool was questionnaire & data analysis was done by using LISREL and PLS softwares. In this regard, 200 senior executives in the studied population were selected by multistage cluster sampling. The results show that transformational leadership has significant effect on both market and entrepreneurial tendencies; but evidence suggests a lack of support for themediating role of market orientation in the relationship between transformational leadership & marketing capabilities; and confirming the indirect impact of transformational leadership on developing marketing capabilities & performance improvement merely through the entrepreneurship orientation in our studied businesses.